The Effects of Olive Leaf Extract Administration on the Cerebral Hypoperfusion-Induced Electrophysiological Alterations in Rat Heart - Mehrnoush Moghaddasi; Majid Taati; Hasan Noroozi; Sam Bamani Lirgeshasi; Soheila Pourkhodadad; Bahram Delfan; Afshin Nazari * (Lorestan University of Medical Sciences, 2017)
Background and Aim: In the present study, the role of ethanolic extract of olive (Olea europaea) leaf administration against the cerebral hypoperfusion-induced electrophysiological alterations and left ventricular thickness in rat heart was studied. Materials and Methods: The right carotid artery was occluded with a 5-0 silk suture and the left carotid artery was occluded after a week. The olive (Olea europaea) leaf extract was administered orally (by gavage) to three experimental groups of rats in 100, 200 and 300 mg/kg/day for two weeks after the left carotid artery occlusion and processed in 25 days. The sham and hypoperfusion groups were fed with normal saline. Each group had 6 rats. After 25 days, electrophysiological heart parameters, i.e. HR, QTc, QRS duration, QT interval, PR interval, RR interval, ST amplitude, T wave amplitude and also the thickness of left ventricle (TLV) were assessed. Results: The administration of olive leaf extract (100, 200 and 300 mg/kg) exhibited its cardioprotective effect by both stabilizing heart rate and preventing ECG changes (such as shortening of PR, QRS, QT and QTc intervals, prominent T waves and ST elevation). Moreover, olive leaf extract (100, 200 and 300 mg/kg) prevented cardiac hypertrophy after cerebral hypoperfusion. Conclusion: Our results indicated that post-treatment with ethanolic extract of olive leaves could prove beneficial effects in managing the cerebral hypoperfusion-induced cardiac abnormality in rats.